A phase 2 study of venetoclax plus R-CHOP as first-line treatment for patients with diffuse large B-cell lymphoma - Morschhauser, Franck; Feugier, Pierre; Flinn, Ian W; Gasiorowski, Robin; Greil, Richard; Illés, Árpád; Johnson, Nathalie A; Larouche, Jean-François; Lugtenburg, Pieternella J; Patti, Caterina; Salles, Gilles A; Trněný, Marek; et al. (Blood, 2021)
The phase 2 CAVALLI (NCT02055820) study assessed efficacy and safety of venetoclax, a selective B-cell lymphoma-2 (Bcl-2) inhibitor, with rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) in first-line (1L) diffuse large B-cell lymphoma (DLBCL), including patients demonstrating Bcl-2 protein overexpression by immunohistochemistry (Bcl-2 IHC+). Eligible patients were ≥18 years of age and had previously untreated DLBCL, Eastern Cooperative Oncology Group performance status ≤2, and International Prognostic Index 2 to 5. Venetoclax 800 mg (days 4-10, cycle 1; days 1-10, cycles 2-8) was administered with rituximab (8 cycles) and cyclophosphamide, doxorubicin, vincristine, and prednisone (6-8 cycles) in 21-day cycles. Primary end points were safety, tolerability, and research_plete response (CR) at end of treatment (EOT). Secondary end points were progression-free survival (PFS) and overall survival. Comparative analyses used covariate-adjusted R-CHOP controls from the GOYA/BO21005 study, an appropriate contemporary benchmark for safety and efficacy. Safety and efficacy analyses included 206 patients. CR rate at EOT was 69% in the overall population and was maintained across Bcl-2 IHC+ subgroups. With a median follow-up of 32.2 months, trends were observed for improved investigator-assessed PFS for venetoclax plus R-CHOP in the overall population (hazard ratio [HR], 0.61; 95% confidence interval [CI], 0.43-0.87) and Bcl-2 IHC+ subgroups (HR, 0.55; 95% CI, 0.34-0.89) vs R-CHOP. Despite a higher incidence of grade 3/4 hematologic adverse events (86%), related mortality was not increased (2%). Chemotherapy dose intensity was similar in CAVALLI vs GOYA. The addition of venetoclax to R-CHOP in 1L DLBCL demonstrates increased, but manageable, myelosuppression and the potential of improved efficacy, particularly in high-risk Bcl-2 IHC+ patient subgroups.
Keywords: senioři; difúzní velkobuněčný B-lymfom; únava; Doxorubicin; Neoplasm Proteins; Hematologic Diseases; cyklofosfamid; senioři nad 80 let; gastrointestinální nemoci; prednison; nádorové proteiny; Gastrointestinal Diseases; mladiství; Kaplan-Meier Estimate; geny bcl-2; Middle Aged; Genes, bcl-2; mužské pohlaví; Kaplanův-Meierův odhad; Adult; mladý dospělý; Bridged Bicyclo Compounds, Heterocyclic; Fatigue; Vincristine; sulfonamidy; Lymphoma, Large B-Cell, Diffuse; infekce; faktor stimulující kolonie granulocytů; Aged, 80 and over; krevní nemoci; Young Adult; Rituximab; doxorubicin; ženské pohlaví; Sulfonamides; Cyclophosphamide; Humans; Proto-Oncogene Proteins c-bcl-2; Prednisone; Infections; rituximab; lidé středního věku; protoonkogenní proteiny c-bcl-2; vinkristin; Antineoplastic Combined Chemotherapy Protocols; Granulocyte Colony-Stimulating Factor; protokoly protinádorové kombinované chemoterapie; bicyklické sloučeniny heterocyklické; dospělí; Female; Aged; Adolescent; lidé; Male